Comparing the Effects of Eight-Week Corrective Selective Exercises on Kyphosis Abnormality Prior to and Following Puberty among the Girls Attending High Schools in Boroojerd, Lorestan - Bashirinia, Soghra (Ciência e Natura, 2015)
The aim of this study was to compare the effects of eight weeks selected corrective exercise on kyphosis deformity before and after puberty in girls is Boroojerd city. According to the study, pre-test and post-test experimental and control groups, and independent and dependent variable is the type of quasi-experimental research survey of all elementary and secondary school students will form Boroojerd city. Using cluster sampling - a random number 1200 from 7 schools (450 schools, 750 elementary students) with the use of raster lines were evaluated plummet a total of 44 patients (24 person puberty prepubescent and 20 person after maturity) with kyphosis deformity, were selected as research subjects after obtaining informed consent and completed questionnaires, their kyphosis using flexible ruler and balance range to be measured by the stork balance test Then the four groups, 24 person before maturity (12 person group control and 12 group experimental), 20 person after maturity(10 person group control, 10 person group experimental) were classified then subjects experimental group eight weeks, 3 sessions a week, each session 30-45 minutes the program of corrective exercises (stretching and strengthening) were after completion of training, all subjects (control groups and Experimental before and after puberty) the tests were And test results independent T-test and dependent t- test the analysis. The result showed That There was no signification difference between 8 weeks corrective training on kyphosis deformity (p=0.12) pre-and post-pubertal girls students. But the practice effect on the improvement of kyphosis ago (p = 0.02) and after puberty (0.03) girls students had a significant impact.